Battleship Potemkin : from the series "The year 1905" - d; Agadzhanova, Nina Ferdinandovna, 1889-1974; Eisenstein, Sergei, 1898-1948; Antonov, Aleksandr Pavlovich, 1898-1962 ([United States] : [Kino International], 1925)
Based on the historical events and events of the mutiny in the Russian warship Potemkin, which began as a simple protest by the crew over the supply of rotten meat for dinner and led to a street demonstration in the Port of Odessa, which resulted in a massacre.--
Alexander Antonov, Grigori Alexandrov, Vladimir Barski, Mikhail Gomorov, Aleksandr Levshin.
Head cinematographer, Eduard Tisse ; reconstruction under the direction of Enno Patalas in collaboration with Anna Bohn ; film editing, Sala Deinema ; colorization, Gerhard Ullmann ; English title editing, Ron Heidt ; music (1926), Edmund Meisel ; adaptation and instrumentation (2005), Helmet Imig.
Silent film with Spanish intertitles or Russian intertitles.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed June 16, 2022)
Keywords: v; Mutiny -- Drama; Sailors -- Drama; Historic ships -- Drama; Navies -- Officers -- Drama; Odesa (Ukraine) -- Drama; Russia -- History -- 1801-1917 -- Drama; Russia -- History -- Revolution, 1905-1907 -- Drama; Motion pictures; Feature films; Fiction films; Silent films; Video recordings for the hearing impaired; War films; Historical films; Streaming video